Babak Akhir Penderitaan, Dosa dan Teodice dalam Epilog Kitab Ayub 42:7-17 - Rumbi, Frans Paillin (Sekolah Tinggi Teologi Kanaan Nusantara, 2019)
Does sin cause suffering? Why do the righteous suffer? That is the general picture of the book of Job. To answer this problem, the author wants to examine the epilogue section of the book of Job (42: 7-17). The interpretation method used in this paper is the narrative approach. In the epilogue of the book of Job, it appears that God restored Job's suffering, forgiven his mistakes and also forgave friends who had acted as if defending God. Some of the findings of this study include: (1) Suffering is not always a punishment from God. (2) God sided with and defended those who suffered. (3) Pastoral assistance becomes bland if the victims are placed on the guilty side, without trying to get them out of life's difficulties. (4) God uses those who suffer to ask forgiveness for those who feel themselves as righteous people. Apakah dosa mengakibatkan penderitaan? Mengapa orang benar menderita? Itulah gambaran umum dari kitab Ayub. Untuk menjawab persoalan tersebut, maka penulis hendak mengkaji bagian epilog kitab Ayub (42:7-17). Adapun metode penafsiran yang digunakan adalah pendekatan naratif. Pada epilog tampak bahwa Allah memulihkan penderitaan Ayub, mengampuni kesalahannya dan juga mengampuni para sahabat yang telah bertindak seolah-oleh membela Allah. Beberapa temuan penelitian ini antara lain: (1) Tidak selamanya penderitaan merupakan hukuman dari Allah. (2) Allah berpihak dan membela orang yang menderita. (3) Pendampingan pastoral menjadi hambar kalau para korban ditempatkan pada pihak yang bersalah, tanpa usaha membawa mereka keluar dari kesulitan hidup. (4) Allah menggunakan mereka yang menderita untuk meminta pengampunan bagi orang yang merasa benar.